Mencegah Hipotermia pada Bayi Prematur: Peran Kasur Transportasi Bayi - Nurhayati; Nyimas Heny Purwati; Anita Aprilawati (NERS Jurnal Keperawatan, 2025)
Background: Premature infants transported from the operating room to the neonatal care unit are at high risk of hypothermia. This study aimed to evaluate the effectiveness of infant transport mattress combined with polyethylene wraps in preventing hypothermia during neonatal transport. Methods: This quasi-experimental study used an accidental sampling method; 52 premature infants with a gestational age <37 weeks and birth weight <2500 grams were randomly allocated into two groups: 26 infants in the intervention group (transport mattress + polyethylene wrap) and 26 infants in the control group (polyethylene wrap only). Body temperatures were measured immediately before transport and upon arrival at the neonatal care unit. Data were analyzed using SPSS ver. 27.0. Results: In the intervention group, there was a statistically significant increase in body temperature before (36.5(35.0-37.1)ºC) and after transport (36.7(36.0-37.1)ºC), p=0.001, while in the control group there was a significant decrease in body temperature before (36.5(36.0-36.9)ºC) and after transport (36.0(34.0-37.0)ºC), p=0.002. Discussion: The use of an infant transport mattress, in addition to standard polyethylene wrapping, significantly improves thermal stability in premature infants during transport. Healthcare facilities are encouraged to incorporate this intervention into neonatal transport protocols to reduce the risk of hypothermia and associated complications